Portugal, the European Union and the crisis - Sousa,Teresa de (2018)
The two crises the national and the European crisis changed the terms of reference of the strategic debate in Portugal and, for the first time since the Maastricht Treaty, there was again a domestic debate on Portuguese foreign policies. The Portuguese elites trust in the future of Europe (and in their own European future) was called into question. European integration had been seen as an irreversible project, the Euro was supposed to be immune to crisis and the European Union was represented as one of the crucial poles of the international system; however, the last years have shown a more complex reality.